Biological functions of MAIT cells in tissues - Klenerman, P; Hinks, TSC; Ussher, J (Elsevier, 2020)
Mucosal associated invariant T (MAIT) cells have a recognised innate-like capacity for antibacterial host defence, consequent on the specificity of their T cell receptor (TCR) for small molecule metabolites produced by a range of prokaryotic and fungal species, their effector memory phenotype, and their expression of cytotoxic molecules. However, recent studies have identified at least two other important functions of MAIT cells in antiviral immunity and in tissue homeostasis and repair. Each are related to distinct transcriptional programmes, which are activated differentially according to the specific immune context. Here we discuss these diverse functions, we review the evidence for the newly identified role of MAIT cells in promoting tissue repair, and we discuss emerging data pointing to the future directions of MAIT cell research including roles in cancer, in antiviral immunity and recent studies in the immune response to SARS-CoV-2 infection. Overall these studies have made us aware of the potential for pleiotropic roles of MAIT cells and related cell populations in micee and humans, and have created a simple and attractive new paradigm for regulation in barrier tissues, where antigen and tissue damage are sensed, integrated and interpreted.